Security Challenges and Solutions in Kubernetes Container Orchestration - Princess Egbuna, Oluebube (Journal of Science & Technology, 2022)
This study aims to uncover vulnerabilities, provide practical mitigation measures, and highlight policy implications by examining the security issues and solutions associated with Kubernetes container orchestration. The key aims include investigating vulnerabilities in Kubernetes components, reviewing network security risks, evaluating container runtime vulnerabilities, and studying risks related to third-party integrations. This research is based on a thorough analysis of case studies and existing literature, emphasizing new threats and security vulnerabilities in Kubernetes deployments. Important discoveries point to runtime vulnerabilities in container environments, network security holes caused by misconfigurations, and significant vulnerabilities in Kubernetes control plane components. The policy implications highlight the necessity of improving Kubernetes’s security procedures through industry standards, regulatory frameworks, and ongoing training. Organizations may better safeguard Kubernetes deployments against changing threats by implementing robust authentication procedures, network policies, and runtime protection measures. With its findings and suggestions for enabling safe container orchestration in contemporary IT infrastructures, this study adds to the current conversation around Kubernetes security.